PENERAPAN METODE SINGLE EXPONENTIAL SMOOTHING DALAM PENGEMBANGAN APLIKASI PREDIKSI JUMLAH SISWA BARU: Indonesia - nurfitriani, Nurfitriani; Murniati, Wafiah; Ashari, Maulana Ashari; Fadli, Sofiansyah Fadli (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2022)
The vocational Forecasting process is an important thing for the Forecasting process to determine new students to obtain data and information on the number of prospective new students who will register. Darussalam Islamic Vocational School does not yet have a Forecasting application so predicting the number of students is still conventional which causes school to be unable to plan for future needs. Therefore the Forecasting applications are needed. The purpose of this study is to produce an application to make it easier for schools to predict the number of new students in the future. This research method uses the Single Exponential Smoothing method, while the development method uses the Waterfall. method. In this study, Testing. will be carried out using a Black-Box involving users, namely the principal and of school study program. The test consists of 4 aspects of Testing, namely the login process, the import process, the process of adding data, the process of Forecasting the number of new students. With the Forecasting application. the number of new students that have been MAD can predict the number of students who will register in the following year based on previous data.